IMPLEMENTATION OF SECURITY STANDARDS IN RESIDENTIAL BLOCKS REVIEWED FROM THE PERSPECTIVE OF STATIC SECURITY SYSTEMS AT AMBARAWA CLASS IIA CORRECTIONAL FACILITY - Saputro, Nugroho Bowo; Indahdewi, Lauditta (Universitas Nusa Cendana, 2025)
This study aims to analyze the implementation of security standards in the residential blocks of the Ambarawa Class IIA Correctional Facility, particularly from the perspective of static security systems. Static security systems include physical facilities and infrastructure used to ensure security within the residential block environment, such as boundary walls, doors, bars, and surveillance systems. This research employs a qualitative approach using observation, interviews, and document studies to collect data. The results indicate that the implementation of security standards at the Ambarawa Class IIA Correctional Facility has been in accordance with existing regulations. However, some areas still require improvement, particularly in terms of infrastructure maintenance and the modernization of surveillance technology. The study recommends providing training for officers to optimize their surveillance duties and accelerate the planned relocation process. These measures are expected to help maintain security and order in the residential blocks. Keywords: Static Security Systems; Security Standards; Correctional Facility